Review of Invertebrate Biological Control Agents Introduced into Europe. - Gerber, Esther; Schaffner, Urs. (Oxford : CAB International, 2016)
This book provides an overview of all documented releases of exotic (non-European) invertebrate biological control agents (IBCAs) into the environment in Europe and summarizes key information on the target species as well as on the biological control agent released.
1.39.1 Closterocerus cinctipennis Ashmead (Hym., Eulophidae).
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books